Efektivitas Model Pembelajaran Problem Solving terhadap Kemampuan Pemecahan Masalah Matematis Siswa SMA - Megasari; Nur Wahyuni Akhmar; Arsyad L; Sumardin Raupu; Lisa Aditya Dwiwansyah Musa (AB-JME: Al-Bahjah Journal of Mathematics Education, 2026)
Mathematical problem solving ability is one of the important competencies in mathematics learning, but this ability is still not optimal in high school students. This study aims to determine the effectiveness of the Problem Solving learning model on the mathematical problem solving ability of class X students of SMAN 5 Palopo. This study uses a quantitative approach with a quasi-experimental type and a nonequivalent control group design. The research sample consisted of class X N7 as an experimental group totaling 32 students and class X N6 as a control group totaling 31 students. Data collection techniques used tests, observation, and documentation. The test instrument was in the form of essay questions arranged based on Polya's problem solving indicators, namely understanding the problem, making a plan, implementing the plan, and re-checking the answers. Data were analyzed descriptively and inferentially through normality tests, homogeneity tests, and Independent Samples t-Test. The results showed that the average post-test of the experimental group was 83.40 in the high category, while the control group was 37.45 in the very low category. Student activity reached an average of 93.47% in the very good category. The t-test results showed a significance value <0.001. Thus, the Problem Solving learning model is effective for students' mathematical problem-solving abilities.